Thermal and Interfacial Studies of Binary Alloys of Nicotinamide-b-Naphthol Drug System - Shekhar, H.; Kant, Vishnu (Asian Journal of Chemistry, 2012)
The study reports the thermal and growth investigation of binary alloys represented by nicotinamide with b-naphthol. The solid-liquid equilibrium data determined by Thaw-melt method with their corresponding compositions construct the solid-liquid phase diagram which suggests simple eutectic behaviour is followed by the binary system. The activity coefficient model based on enthalpy of fusion was employed to calculate the excess thermodynamic properties that of gE, hE and sE, which predict the nature of molecular interaction, ordering and stability between the components. The partial and integral mixing functions DGM, DHM, DSM of the eutectic and noneutectic alloys were also computed. The driving force of nucleation during solidification (DGv), critical size or radius (r*) and the critical free energy of nucleation (DG*) at different undercoolings have been determined. Using heat of fusion data the solid-liquid interface energy (s), grain boundary energy (sgb), the Gibbs-Thomson coefficient (t) and roughness parameter (a) of all the alloys are evaluated by numerical method. Interface morphology of the alloys follows the Jackson's surface roughness (a) theory and predicts the faceted growth proceeds in all the alloys.